PHYSICIAN-ASSISTED SUICIDE AS A CONSTITUTIONAL RIGHT: GLUCKSBERG REVISITED - Brade, Alexander (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2023)
“Glucksberg“ is celebrating its 25th anniversary. In 1997, the Supreme Court held that a right to (physician) assisted suicide was not protected by the Due Process Clause of the Fourteenth Amendment. However, the Court was wrong – back then and today. This is not only because of US case-law and US states legislation, but also because of international developments all pointing towards legalizing assisted suicide.